Secondary venous aneurysm following intravenous drug abuse: A case report - Marković, Miroslav; Dragaš, Marko; Končar, Igor; Banzić, Igor; Pejkić, Siniša; Fatić, Nikola; Davidović, Lazar (Vojnosanitetski pregled, 2017)
Introduction. Venous aneurysm (VA) is a rare condition that can be presented in both superficial and deep venous system. Secondary VAs as well as pseudoaneurysms are usually caused by external spontaneous or iatrogenic trauma. They are often misdiagnosed and inadequately treated. Complications include thrombosis, phlebitis, eventual pulmonary embolism and rupture. Case report. We presented a case of secondary VA of the great saphenous vein developed in a young addict following chronic intravenous drug application in the groin region. Aneurysm required urgent surgical treatment due to bleeding complication as it was previously misdiagnosed for hematoma (or abscess) and punctuated by a general surgeon. Complete resection of VA with successful preservation of continuity of the great saphenous vein was performed. Postoperative course was uneventful. Regular venous flow through the great saphenous vein was confirmed on control ultrasound examination. Conclusion. VAs are uncommon, among them secondary VA being extremely rare. In cases with a significant diameter or threatening complications surgical treatment is recommended.
Keywords: aneurysm; saphenous vein; diagnosis; differential; histological techniques; injections; intravenous; opioid-related disorders; vascular surgical procedures